BUDAYA DAN KEARIFAN LOKAL SEBAGAI BENTENG RADIKALISME - Achmad Wahidy (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2017)
Abstract – This his article discussed about the role of culture and values of local wisdom as a bulwark of radicalism that. Pervader all principles of people's live. Culture as a reflection of custom and behavior that incarnate to form a local wisdom is described through the spirit of coorperation, tolerance, and discussion to reach agreement by taking deliberation that is able to maintain the relationship of society life in harmony. By preserving and maintaining the culture and values of local wisdom well in the society life are expected to be contributor in preventing and minimizing the development and growth of radicalism in nation, state, and society life.Keywords: Culture, local wisdom, radicalism